Long‐term safety and efficacy of sustained eculizumab treatment in patients with paroxysmal nocturnal haemoglobinuria. (25th April 2013) - Hillmen, Peter; Muus, Petra; Röth, Alexander; Elebute, Modupe O.; Risitano, Antonio M.; Schrezenmeier, Hubert; Szer, Jeffrey; Browne, Paul; Maciejewski, Jaroslaw P.; Schubert, Jörg; Urbano‐Ispizua, Alvaro; de, Carlos; et al.
Summary Paroxysmal nocturnal haemoglobinuria (PNH) is characterized by chronic, uncontrolled complement activation resulting in elevated intravascular haemolysis and morbidities, including fatigue, dyspnoea, abdominal pain, pulmonary hypertension, thrombotic events (TEs) and chronic kidney disease (CKD). The long‐term safety and efficacy of eculizumab, a humanized monoclonal antibody that inhibits terminal complement activation, was investigated in 195 patients over 66 months. Four patient deaths were reported, all unrelated to treatment, resulting in a 3‐year survival estimate of 97·6%. All patients showed a reduction in lactate dehydrogenase levels, which was sustained over the course of treatment (median reduction of 86·9% at 36 months), reflecting inhibition of chronic haemolysis. TEs decreased by 81·8%, with 96·4% of patients remaining free of TEs. Patients also showed a time‐dependent improvement in renal function: 93·1% of patients exhibited improvement or stabilization in CKD score at 36 months. Transfusion independence increased by 90·0% from baseline, with the number of red blood cell units transfused decreasing by 54·7%. Eculizumab was well tolerated, with no evidence of cumulative toxicity and a decreasing occurrence of adverse events over time. Eculizumab has a substantial impact on the symptoms and complications of PNH and results a significant improvement in patient survival.